Towards white-light emission of fluorescent polymeric nanoparticles with a single luminogen possessing AIE and TICT properties. Issue 2 (12th December 2019) - Hu, Yaxin; Liang, Xiaoqin; Wu, Dongliang; Yu, Bang; Wang, Yijia; Mi, Yifang; Cao, Zhihai; Zhao, Zujin
Abstract : White-light-emitting AIE-PNPs were facilely and efficiently prepared through miniemulsion copolymerization by using an AIE luminogen with twisted intramolecular charge transfer properties as a single emitting component. Abstract : A novel technique of modulating the emission behavior of aggregation-induced emission (AIE) polymeric nanoparticles (AIE-PNPs) based on the polymer matrix was provided. White-light-emitting (WLE) AIE-PNPs were facilely synthesized through miniemulsion copolymerization of methyl methacrylate (MMA) and comonomers with various polarities by using a single luminogen with AIE and twisted intramolecular charge transfer (TICT) properties, (2-(3-cyano-5, 5-dimethyl-4-(4-(1, 2, 2-triphenylvinyl)styryl)furan-2(5 H )-ylidene)malononitrile (TPE-TCF)). The increased or reduced polarity of the polymer matrix could lead to red-shifted or blue-shifted emission of polymer/TPE-TCF AIE-PNPs, respectively. The polarity-dependent emission behavior of polymer/TPE-TCF AIE-PNPs was generally validated in the AIE-PNPs with various polymer matrices. The WLE polymer/TPE-TCF AIE-PNPs could be generally synthesized via miniemulsion copolymerization of MMA with isobornyl methacrylate, stearyl methacrylate, lauryl methacrylate, n -hexyl methacrylate, and cyclohexyl methacrylate at an appropriate monomer composition. By simply coating a layer of prepared WLE AIE-PNPs onto UV LED chips, the UV light could be successfully converted to white light, clearly demonstrating their great application potential in electronic and photonic devices.